Online Pragmatic Language Use in Asperger Syndrome and Learning Disability Discussion Forums - Dansereau, Francesca; Flanagan, Tara (Asian Journal of Social Sciences and Management Studies, 2019)
Research has indicated that self-expression for individuals on the autism spectrum may be facilitated through written language by promoting a more flexible environment within which to express beliefs, opinions, ideologies and expectations—in essence, creating a safe place for communication. Such safe places have burgeoned with the evolution of the Internet, and many individuals with autism have taken the opportunity to express themselves publicly by developing their own virtual communities, some of which have taken place on discussion forums, websites and weblogs. This research study evaluates natural discourse in an Asperger Syndrome discussion forum to explore social communication in the autism spectrum community by using the pragmatic profile questionnaire of the CELF. A discussion forum for individuals with learning disabilities was used to explore similarities and differences in online pragmatic language use among people who self-identified as belonging to one of the two groups. The findings highlight the nuances in pragmatic language use in online discussion forums and the need to consider these skills in context. Researchers and practitioners should refrain from making one-size-fits-all recommendations regarding the creation of supportive social spaces for individuals on the autism spectrum.